STUDY OF THE COMPOSITION AND MAIN CHARACTERISTICS OF PETROLEUM OILS AND THEIR EMULSIONS - Urinbova, Marifatoy; Abdikamalova, Aziza; Ergashev, Oybek; Eshmetov, Izzat; Ismadiyarov, Akmaljon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article considers the stability features of water-petroleum emulsions formed on the basis of oil from the Northern Ortabulak and Northern Shurtan fields. The study was conducted taking into account differences in the composition of oil, including the content of paraffins, resins, asphaltenes and sulfur, as well as under different temperature conditions. It was found that a high concentration of paraffins contributes to a decrease in the stability of emulsions, facilitating demulsification, while resins and asphaltenes increase the stability of emulsions, hindering their destruction. The results obtained provide an opportunity to better understand the mechanism of the influence of oil composition on the demulsification process and can be useful for increasing the efficiency of oil preparation for processing.